(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the results of treating interstitial ectopic pregnancy by laparoscopic surgery at Nghe An Obstetrics and Pediatrics Hospital. Materials and methods: A retrospective, cross-sectional study on 41 patients with unruptured interstitial ectopic pregnancy and indicated for laparoscopic surgery at Nghe An Obstetrics and Pediatrics Hospital from 2020 to 2023. Results: The average β-hCG concentration before surgery was 35333 ± 32948.9 mUI/mL, 92.7% had a good decrease in β-hCG concentration after surgery. 43.9% of cases had a gestational mass size ≥ 3,5cm. Laparoscopic cornual resection accounting for 78.1%. The rate of patients without complications and with good results after surgery was 100%. The average hospital stay after surgery was 4,5 ± 0,9 days. Conclusion: Laparoscopic surgery for interstitial ectopic pregnancy is a method with a high success rate and low complications.